BENEFITS OF EARLY POST-ERCP LAPAROSCOPIC CHOLECYSTECTOMY: A SINGLE CENTRE PROSPECTIVE STUDY - Farhan javed; Saira Saleem; Ayesha Rehman; Faiza Wattoo; Nadia Bano; Nazim Hayat (Journal of University Medical & Dental College, 2021)
ABSTRACT: BACKGROUND & OBJECTIVE: Laparoscopic cholecystectomy (LC) following Endoscopic retrograde cholangiopancreatography (ERCP) is associated with an increased risk of complications. ERCP is associated with increased incidence of complications during LC. Surgery may be performed in same anesthesia with ERCP or up to 6 weeks later. We aimed to determine the benefits of performing LC within 72hrs of ERCP. METHODOLOGY: After institutional ethical approval this prospective cross-sectional study was performed at Madinah Teaching Hospital Faisalabad from April 2019 to June 2020. By performing convenience sampling, all patients undergoing LC after uneventful ERCP in our hospital were included. Study population was divided based on interval between ERCP and Cholecystectomy; Group-A had LC within 72hrs of ERCP, Group B had LC in same hospital stay after 72hrs and Group-C patients were discharged after ERCP and readmitted for LC. Data was collected using custom designed questionnaire, tabulated using Microsoft Excel 2016 and subjected to statistical tests to compare outcomes. Primary outcome was incidence of complications, while operative time, hospital stay and cost were considered as secondary outcomes. p-value of <0.05 was considered significant. RESULTS: Total 75 patients were included in study, 32 in Group-A, 20 in Group-B and 23 in Group-C. Average age was 44.987 ± 14.819 and study population was predominantly female (86.67%). Complication rate, duration of hospital stay and average cost were less in Group A as compared to other groups (p<0.05). Mean operative time in 3 groups was similar. CONCLUSION: LC within 72hrs after ERCP provides superior results in terms of fewer complications, shorter hospital stays and lesser cost.